Analisis Penggunaan Ejaan dan Kalimat Efektif pada Teks Opini dalam Laman Website “Poskota” Edisi Januari 2024 sebagai Kelayakan Bahan Bacaan dan Sumber Informasi - Adinda Dewi Larasati Ismailia; Nazwa Salsabila; Eka Putri Widiyastuti; Caroline Audrey Madyalina; Nawang Wulan; Adinda Cindy Aryanti; Asep Purwo Yudi Utomo; Qurrota Ayu Neina (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
Syntax is branch of linguistics that studies grammar and sentence structure, including the rules for arranging words and phrases to form effective sentences. In this article, syntax plays a role in assessing the effectiveness of sentences in opinion texts. This research focuses on analyzing the use of spelling and effective sentences in opinion text published on the January 2024 edition of the “Poskota” website. The purpose of this article is to evaluate that the opinion text meets good and correct linguistic standards, so that it can be considered as reading material and a reliable source of information. The research method used is descriptive qualitative method with text analysis approach. The research data is in the form of identification results in opinion texts published on the “Poskota” page during January 2024. The data collection techniquesused were listening and recording; the focus of data collection was on spelling errors, sentence structure, and the effectiveness of conveying ideas. The data presentation technique uses an informal method supported by tables to provide a broader picture of the research results. The result of the analysis is 41 sentences consisting of 51 errors in sentences that refer to sentence ineffectiveness and 11 sentences that contain spelling errors. In the opinion text entitled “Etika politik dan Netralitas Presiden” there are 21 errors in sentences that refer to sentence ineffectiveness and 5 sentences that contain spelling errors. In the opinion text entitled “Kekerasan Vs Netralitas dalam Pesta Demokrasi” there are 29 errors that refer to sentence ineffectiveness and 11 sentences with spelling errors. In this study, ineffectiveness in sentences is classified into 4, namely inaccurate use of spelling, economical use of word, incnsistency of informnation, and inaccurate use of words. As a sample, in this analysis the researcher uses one of the opinion texts entitled “Kekerasan Vs Netralitas dalam Pesta Demokrasi”. The results of the analysis of the opinion text contained 29 errors referring to sentences ineffectiveness and 11 sentences with spelling errors. This research is useful for improving understanding and skills in the use of spelling errors. This research is useful for improving understanding and skills in the use of spelling that is in accordance with the rules of language and effective sentences construction.